A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material
By using the preparation method of ruthenium/molybdenum dioxide composite in the electrolytic water hydrogen production electrode material, the existing problem of poor catalytic performance is solved, efficient electrolytic water hydrogen production performance is achieved, and the process flow is simplified and the reduction is cost.
Patent Information
- Application Number
- CN202211651932.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The catalytic performance of existing electrolytic water hydrogen production electrode materials is poor, resulting in low efficiency of electrolytic aquatic hydrogen production, and it is difficult for existing methods to effectively prepare pure MoO2/Ru composite materials.
A preparation method of hydrogen production electrode material for ruthenium/molybdenum dioxide electrolyzed water is adopted. By stirring and mixing ruthenium trichloride and molybdenum pentachloride in deionized water, adding polyvinylpyrrolidone to constant temperature treatment, and then removing unreacted Organic substances and inorganic ions are finally obtained by annealing reduction treatment to obtain a ruthenium/molybdenum dioxide composite material.
It has achieved efficient preparation of ruthenium/molybdenum dioxide electrolytic hydrogen production electrode material, with excellent electrolytic hydrogen production performance, and has simple process, few steps, short time consumption, low cost, uniform composition, and controllable morphology.
Smart Images

Figure CN115928142B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of electrode materials for hydrogen production by water electrolysis, and in particular to a method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material. Background Art
[0002] With the continuous advancement of industrialization, the consumption of fossil fuels has increased dramatically, and the problems of energy shortage, greenhouse effect and environmental pollution have become increasingly prominent. Finding new renewable clean energy has become the focus of everyone's attention. H2 is a clean energy with a high calorific value and is very popular. However, the content of H2 in nature is extremely limited, so artificial preparation of H2 is the key to its large-scale application. Among them, water electrolysis has attracted much attention as a green method of producing H2, but its consumption of electricity is also huge. At present, the biggest challenge facing the electrolysis of water to produce hydrogen is how to maximize the efficiency of hydrogen production and thus reduce the consumption of electricity. To this end, finding efficient electrode materials for the electrolysis of water to produce hydrogen has become the common goal of the majority of scientific researchers.
[0003] So far, there have been reports on ruthenium-based electrocatalytic hydrogen production electrode materials. For example, Liu et al. found that Ru / MoO2-modified carbon nanotubes have excellent water electrolysis performance, with a flow rate of 10 mA / cm in 0.5 M H2SO4 solution. 2 The overpotential under current density is only 16mV (L.Liu et al., Int.J.HydrogenEnerg, 2022, 47, 26978-26986). Chen's research group prepared molybdenum trimethylenetetracarboxylate first, then added RuCl3 to the molybdenum trimethylenetetracarboxylate solution, and finally prepared Ru-MoO2 nanostructure by annealing in N2. The structure also showed good electrolysis properties, with a current of 10mA / cm in 0.5M H2SO4 solution. 2 The overpotential under current density is only 55mV (P. Jiang et al., J. Mater. Chem. A 2017, 5, 5475-5485). However, the former is a composite structure of Ru / MoO2 / C, and requires C nanotubes as the framework of the entire system. Its good water electrolysis performance is also inseparable from the assistance of C nanotubes (the article shows that in the sample without C nanotubes, its 10mA / cm in 0.5M H2SO4 solution 2 The overpotential under current density rises to about 100mV). The latter has a complicated preparation procedure and takes a long time. The preparation of molybdenum benzene trimeate takes up to 7 days, plus the vacuum drying (12h), co-dissolution with RuCl3 (10h) and annealing time (3h), which takes even longer. More importantly, from the results of element mapping, the distribution of Ru on the MoO2 surface is not uniform.
[0004] CN 111468144 A discloses a MoS2 / MoO2 / Ru composite material and a preparation method thereof. The method uses nano MoS2 and water-soluble Ru salt as precursors and synthesizes the composite material through decomposition, grinding and calcination. The method comprises the following steps: adding nano MoS2 to water, uniformly dispersing the composite material by ultrasonication under ice bath conditions, and then placing the ultrasonically dispersed mixed solution in a cell crusher for ultrasonication for at least 30 minutes; sequentially adding water-soluble Ru salt and H2O2 with a concentration of 4-6wt% to the obtained mixed solution and stirring the mixed solution uniformly, controlling the temperature at 80-95°C to react for 4-6 hours, centrifuging, washing and drying to obtain a MoS2 / RuO2 composite material; fully grinding the prepared MoS2 / RuO2 composite material uniformly, calcining it at 400-800°C for 3-6 hours under N2 gas or inert atmosphere, and naturally cooling it to room temperature to obtain a MoS2 / MoO2 / Ru composite material. Although the sample contains MoO2 / Ru components, it also contains MoS2, and the method does not mention the synthesis steps of the MoO2 / Ru composite structure. It is proved that this method is not suitable for the preparation of MoO2 / Ru composites.
[0005] CN113584504 A discloses a Ru / RuO2 / MoO2 composite material and its preparation method and application. (NH4)2MoS4 is added to a RuO2 colloidal suspension, and after ultrasonic treatment, hydrazine hydrate is added and stirred evenly. The resulting mixed solution is kept at 150-240°C for 4-48 hours, centrifuged, washed, and dried to obtain a RuO2 / MoS2 composite material; the RuO2 / MoS2 composite material is fully ground and evenly, calcined at 200-1000°C under N2 gas or inert atmosphere for 1-12 hours, and naturally cooled to room temperature to obtain a Ru / RuO2 / MoO2 composite material. Although the method contains MoO2, Ru and RuO2 components, there is no synthesis step of MoO2 / Ru. In view of the defects of the method, it is also impossible to prepare a MoO2 / Ru composite material.
[0006] So far, there is no controllable synthesis of pure MoO2 / Ru. Summary of the invention
[0007] In order to solve the technical problem of poor ORR performance of existing catalytic materials, the present invention provides a method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0010] S1, adding ruthenium trichloride into deionized water and stirring until it is completely dissolved to obtain a first mixed solution;
[0011] S2, stirring and mixing molybdenum pentachloride and the first mixed solution to obtain a second mixed solution;
[0012] S3, stirring and mixing polyvinyl pyrrolidone and the second mixed solution to obtain a third mixed solution;
[0013] S4, placing the third mixed solution in a reaction kettle, subjecting the reaction kettle to constant temperature treatment and then naturally cooling it to obtain a reactant;
[0014] S5, removing unreacted organic matter and inorganic ions in the reactants, and drying the washed reactants to obtain black powder;
[0015] S6. Perform annealing and reduction treatment on the black powder to obtain a ruthenium / molybdenum dioxide composite material.
[0016] Furthermore, the purity of ruthenium trichloride in S1 is 96-98%.
[0017] Furthermore, in S5, unreacted organic matter and inorganic ions in the reactants are removed, and the washed reactants are dried to obtain black powder. The specific method is as follows: the reactants are centrifugally washed with ethanol to remove unreacted organic matter, and then the washed reactants are centrifugally washed again with a mixed solution of ethanol and water to remove unreacted inorganic ions, and the washed reactants are dried in an oven to obtain black powder.
[0018] Furthermore, the specific method of annealing and reducing the black powder in S6 to obtain a ruthenium / molybdenum dioxide composite material is as follows: grinding the black powder, and then placing it in a tubular furnace for reduction reaction at a temperature greater than 500°C in H2 or a mixture of H2 and other inert gases for more than 2 hours, allowing it to cool naturally after the reaction is complete, and waiting to cool to obtain a ruthenium / molybdenum dioxide composite material.
[0019] Furthermore, the purity of molybdenum pentachloride in S2 is 99.5% to 99.9%.
[0020] Furthermore, the molecular weight of polyvinyl pyrrolidone in S3 is 57,000-59,000.
[0021] Furthermore, the temperature of the oven in S5 is 40-60°C.
[0022] Furthermore, the mixing ratio of ethanol and water in S5 is 6:4 to 9:1.
[0023] Furthermore, the temperature of the constant temperature treatment in S4 is 170-190° C., and the time is 7.5-8.5 hours.
[0024] Furthermore, the centrifugal speed in S5 is 10000-15000 rpm.
[0025] The advantages and positive effects of the present invention are: the present invention can prepare ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode materials, wherein the electrode prepared from the raw materials RuCl3·xH2O and MoCl5 has the most excellent water electrolysis hydrogen production performance; and the preparation process is simple, with fewer steps, short time consumption, low cost, uniform composition, controllable morphology, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD pattern of various products obtained in Examples 1 to 3 of the present invention;
[0027] Figure 2 is a scanning (SEM) morphology image of the product obtained in Example 1 of the present invention;
[0028] Figure 3 This is a scanning (SEM) morphology image of the product obtained in Example 2 of the present invention;
[0029] Figure 4 This is a scanning (SEM) morphology image of the product obtained in Example 3 of the present invention;
[0030] Figure 5 The polarization curves of ruthenium / molybdenum dioxide and commercial Pt / C water electrolysis obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
[0032] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0033] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.
[0034] Embodiment 1
[0035] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0036] S1. Weigh 0.104 g of ruthenium trichloride (RuCl3·xH2O) and place it in 20 ml of deionized water and stir it thoroughly until it is completely dissolved to obtain a first mixed solution; wherein the purity of ruthenium trichloride is 97%;
[0037] S2, pouring 0.137g of molybdenum pentachloride (MoCl5) into the first mixed solution, stirring for 30 minutes and then mixing to obtain a second mixed solution; wherein the purity of the molybdenum pentachloride is 99.9%;
[0038] S3, stirring 0.05 g of polyvinyl pyrrolidone (PVP) and the second mixed solution for 30 minutes to obtain a third mixed solution; wherein the molecular weight of the polyvinyl pyrrolidone is 58000;
[0039] S4, placing the third mixed solution in a 50 ml reactor, placing the reactor in a 190° C. oven for 8 h of constant temperature treatment, and then cooling naturally to obtain a reactant;
[0040] S5, centrifugally washing the reactant with ethanol to remove unreacted organic matter, then centrifugally washing the washed reactant again with a mixed solution of ethanol and water, repeating 3 times to remove unreacted inorganic ions, and drying the washed reactant in an oven at 60° C. to obtain a black powder; wherein the mixing ratio of ethanol to water is 6:5, and the centrifugal speed is 13000 rpm;
[0041] S6. Grind the black powder and then place it in a tubular furnace for reduction reaction in H2 gas at 500°C for 2 hours. After the reaction is complete, allow it to cool naturally and wait for cooling to obtain a ruthenium / molybdenum dioxide composite material.
[0042] Figure 2 This is a SEM photo of the tetragonal molybdenum dioxide prepared in Example 1. As can be seen from the figure, its morphology is a thin sheet structure and a flower-like structure composed of sheet structures.
[0043] Embodiment 2
[0044] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0045] S1. Weigh 0.275 ml of ruthenium trichloride (RuCI3·xH2O) and place it in 20 ml of deionized water and stir it thoroughly until it is completely dissolved to obtain a first mixed solution; wherein the purity of ruthenium trichloride is 97%;
[0046] S2, pouring 0.267g of molybdenum pentachloride (MoCI5) into the first mixed solution, stirring for 30 minutes and then mixing to obtain a second mixed solution; wherein the purity of the molybdenum pentachloride is 99.9%;
[0047] S3, stirring 0.05 g of polyvinyl pyrrolidone (PVP) and the second mixed solution for 30 minutes to obtain a third mixed solution; wherein the molecular weight of the polyvinyl pyrrolidone is 58000;
[0048] S4, placing the third mixed solution in a 50 ml reactor, placing the reactor in a 190° C. oven for 8 h of constant temperature treatment, and then cooling naturally to obtain a reactant;
[0049] S5, the reactant is centrifuged and washed with ethanol (alcohol) to remove unreacted organic matter, and then the washed reactant is centrifuged again with a mixed solution of ethanol and water, and the process is repeated 3 times to remove unreacted inorganic ions, and the washed reactant is dried in an oven at 60° C. to obtain a black powder; the mixing ratio of ethanol and water is 9:1, and the centrifugal speed is 15,000 rpm;
[0050] S6. Grind the black powder, and then place it in a tubular furnace for reduction reaction at 500° C. for 2 hours using H 2 gas. After the reaction is complete, allow it to cool naturally and wait for cooling to obtain a ruthenium / molybdenum dioxide composite material.
[0051] Figure 3 This is a SEM photo of the tetragonal molybdenum dioxide prepared in Example 2. As can be seen from the figure, the flaky nanosheet structure is very obvious.
[0052] Embodiment 3
[0053] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0054] S1. Weigh 0.208 g of ruthenium trichloride (RuCl3·xH2O) and place it in 20 ml of deionized water and stir it thoroughly until it is completely dissolved to obtain a first mixed solution; wherein the purity of ruthenium trichloride is 97%;
[0055] S2, pouring 0.189g of molybdenum pentachloride (MoCI5) into the first mixed solution, stirring for 30 minutes and then mixing to obtain a second mixed solution; wherein the purity of the molybdenum pentachloride is 99.9%;
[0056] S3, stirring 0.05 g of polyvinyl pyrrolidone (PVP) and the second mixed solution for 30 minutes to obtain a third mixed solution; wherein the molecular weight of the polyvinyl pyrrolidone is 58000;
[0057] S4, placing the third mixed solution in a 50 ml reactor, placing the reactor in a 190° C. oven for 8 h of constant temperature treatment, and then cooling naturally to obtain a reactant;
[0058] S5, the reactant is centrifuged and washed with ethanol to remove unreacted organic matter, and then the washed reactant is centrifuged again with a mixed solution of ethanol and water, and the washing is repeated 3 times to remove unreacted inorganic ions, and the washed reactant is dried in an oven at 60° C. to obtain a black powder; the mixing ratio of ethanol and water is 6:5, and the centrifugal speed is 10000 rpm;
[0059] S6. Grind the black powder, and then place it in a tubular furnace for reduction reaction at 500° C. for 2 hours using a mixture of H2 and other inert gases. After the reaction is complete, allow it to cool naturally and wait for cooling to obtain a ruthenium / molybdenum dioxide composite material.
[0060] Figure 4 This is a SEM photo of the hexagonal ruthenium prepared in Example 3. It can be seen from the figure that the sample is a nanoparticle structure.
[0061] in, Figure 1 The XRD patterns of the products prepared in Examples 1, 2 and 3 are presented. The diffraction peaks thereof correspond well to the hexagonal phase of ruthenium (JCPDS NO.6-663) and the tetragonal phase of molybdenum dioxide (JCPDS NO.2-422). It can be determined that the obtained samples are pure ruthenium / molybdenum dioxide composite structures. Figure 1 The green curve in the middle is the XRD diagram of the product prepared in Example 3. Its diffraction peak corresponds well to that of hexagonal ruthenium (JCPDS NO.6-663), so it can be determined that the obtained sample is pure hexagonal ruthenium.
[0062] Embodiment 4
[0063] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0064] S1. Weigh 0.265 ml of ruthenium trichloride (RuCl3·xH2O) and place it in 20 ml of deionized water and stir it thoroughly until it is completely dissolved to obtain a first mixed solution; wherein the purity of ruthenium trichloride is 96%;
[0065] S2, pouring 0.257g of molybdenum pentachloride (MoCI5) into the first mixed solution, stirring for 30 minutes and then mixing to obtain a second mixed solution; wherein the purity of the molybdenum pentachloride is 99.5%;
[0066] S3, stirring 0.05 g of polyvinyl pyrrolidone (PVP) and the second mixed solution for 30 minutes to obtain a third mixed solution; wherein the molecular weight of the polyvinyl pyrrolidone is 57000;
[0067] S4, placing the third mixed solution in a 50 ml reactor, placing the reactor in an oven at 185° C. for 8.5 h of constant temperature treatment, and then cooling naturally to obtain a reactant;
[0068] S5, the reactant is centrifuged and washed with ethanol to remove unreacted organic matter, and then the washed reactant is centrifuged again with a mixed solution of ethanol and water, and the washing is repeated 3 times to remove unreacted inorganic ions, and the washed reactant is dried in an oven at 40° C. to obtain a black powder; the mixing ratio of ethanol and water is 9:1, and the centrifugal speed is 15000 rpm;
[0069] S6. Grind the black powder, and then place it in a tubular furnace for reduction reaction at 550° C. in H2 or a mixture of H2 and other inert gases for 3 hours. After the reaction is complete, allow it to cool naturally and wait for cooling to obtain a ruthenium / molybdenum dioxide composite material.
[0070] Embodiment 5
[0071] A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material comprises the following steps:
[0072] S1. Weigh 0.218 g of ruthenium trichloride (RuCl3·xH2O) and place it in 20 ml of deionized water and stir it thoroughly until it is completely dissolved to obtain a first mixed solution; wherein the purity of ruthenium trichloride is 98%;
[0073] S2, pouring 0.179g of molybdenum pentachloride (MoCl5) into the first mixed solution, stirring for 30 minutes and then mixing to obtain a second mixed solution; wherein the purity of the molybdenum pentachloride is 99.8%;
[0074] S3, stirring 0.05 g of polyvinyl pyrrolidone (PVP) and the second mixed solution for 30 minutes to obtain a third mixed solution; wherein the molecular weight of the polyvinyl pyrrolidone is 59000;
[0075] S4, placing the third mixed solution in a 50 ml reactor, placing the reactor in a 195° C. oven for 7.5 h of constant temperature treatment, and then cooling naturally to obtain a reactant;
[0076] S5, the reactant is centrifuged and washed with ethanol to remove unreacted organic matter, and then the washed reactant is centrifuged again with a mixed solution of ethanol and water, and the washing is repeated 3 times to remove unreacted inorganic ions, and the washed reactant is dried in an oven at 50° C. to obtain a black powder; the mixing ratio of ethanol and water is 6:4, and the centrifugal speed is 10000 rpm;
[0077] S6. Grind the black powder, and then place it in a tubular furnace for reduction reaction at 600° C. for 2.5 hours using a mixture of H 2 and other inert gases. After the reaction is complete, allow it to cool naturally and wait for cooling to obtain a ruthenium / molybdenum dioxide composite material.
[0078] The experiment of producing hydrogen by electrolyzing water using a ruthenium / molybdenum dioxide composite material includes the following steps:
[0079] Step 1: Prepare 50 mL of 0.5 mol / L H2SO4;
[0080] Step 2: Weigh 0.02 g of the ruthenium / molybdenum dioxide nanosheets synthesized in Example 1 and place them in a mixed solution of 1 mL of ethanol and deionized water, wherein the volume ratio of ethanol to water is 1:4;
[0081] Step 3: Use a pipette to add 8 μL of nafion perfluorinated resin solution to the mixed solution in step 2;
[0082] Step 4: Place the mixed solution in step 3 in an ultrasonic cleaner for 3 minutes to make it evenly dispersed;
[0083] Step 5: Use a pipette to take 5uL of the mixed solution in step 4 and drop it onto a round (3mm diameter) glassy carbon electrode and let it dry naturally. Repeat the above operation 4 times.
[0084] Step 6: Place the electrode prepared in step 5 in the electrolyte prepared in step 1 as a working electrode, use the silver chloride electrode as a reference electrode, and the platinum wire electrode as a counter electrode, test its water electrolysis polarization curve, and calculate its current density.
[0085] Figure 5 The polarization curves of the electrolysis of water of the ruthenium / molybdenum dioxide nanosheets and the commercial Pt / C electrode in Example 1 show that the synthesized ruthenium / molybdenum dioxide nanostructure has a similar overpotential to the commercial Pt / C electrode at a current density of 10 mA / cm2, and has a lower overpotential than the commercial Pt / C electrode as the current density increases, demonstrating that the ruthenium / molybdenum dioxide nanosheets have excellent performance in electrolyzing water to produce hydrogen.
[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material, characterized in that: The following steps are involved: S1, adding ruthenium trichloride into deionized water and stirring until it is completely dissolved to obtain a first mixed solution; S2, stirring and mixing molybdenum pentachloride and the first mixed solution to obtain a second mixed solution; S3, stirring and mixing polyvinyl pyrrolidone and the second mixed solution to obtain a third mixed solution; S4, placing the third mixed solution in a reaction kettle, subjecting the reaction kettle to constant temperature treatment and then naturally cooling the reaction kettle to obtain a reactant, wherein the temperature of the constant temperature treatment is 170-190° C.; S5, removing unreacted organic matter and inorganic ions in the reactants, and drying the washed reactants to obtain black powder; S6. Perform annealing and reduction treatment on the black powder to obtain a ruthenium / molybdenum dioxide composite material.
2. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 1, characterized in that: The purity of ruthenium trichloride in S1 is 96-98%.
3. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 2, characterized in that: In S5, unreacted organic matter and inorganic ions in the reactants are removed, and the washed reactants are dried to obtain a black powder. The specific method is as follows: the reactants are centrifugally washed with ethanol to remove unreacted organic matter, and then the washed reactants are centrifugally washed again with a mixed solution of ethanol and water to remove unreacted inorganic ions, and the washed reactants are dried in an oven to obtain a black powder.
4. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 1, characterized in that: The specific method of annealing and reducing the black powder in S6 to obtain the ruthenium / molybdenum dioxide composite material is as follows: grinding the black powder, and then placing it in a tubular furnace for reduction reaction at a temperature greater than 500°C in H2 or a mixture of H2 and other inert gases for more than 2 hours, allowing it to cool naturally after the reaction is complete, and waiting for cooling to obtain the ruthenium / molybdenum dioxide composite material.
5. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 1, characterized in that: The purity of molybdenum pentachloride in S2 is 99.5% to 99.9%.
6. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 1, characterized in that: The molecular weight of polyvinyl pyrrolidone in S3 is 57,000 to 59,000.
7. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 3, characterized in that: The temperature of the oven in S5 is 40-60°C.
8. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 3, characterized in that: The mixing ratio of ethanol and water in S5 is 6:4 to 9:
1.
9. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 1, characterized in that: The constant temperature time in S4 is 7.5 to 8.5 hours.
10. The method for preparing the ruthenium / molybdenum dioxide water electrolysis hydrogen production electrode material according to claim 3, characterized in that: The centrifugal speed in S5 is 10,000 to 15,000 rpm.
Citation Information
Patent Citations
MoS2 / MoO2 / Ru composite material as well as preparation method and application thereof
CN111468144A
Ru / RuO2 / MoO2 composite material as well as preparation method and application thereof
CN113584504A